The Role of Consumer Pleasure Moderating the Effect of Content Marketing and Price Discount on Online Shopping Decision and Loyalty of Generation Z - Abdul Halik; Mulyanto Nugroho (Media Ekonomi dan Manajemen, 2022)
The phenomenon of the covid 19 pandemics has changed consumer behavior, especially Generation Z who are proficient with social media, but there needs to be a trigger to want to shop at the marketplace. The purpose of this research is to find out empirically about the role of online shopping as mediation, the effect of content marketing, and price discounts on loyalty. consumers, as well as testing consumer pleasure as a moderator. This study uses a population of students who have shopped online at least 3 times using a sample of 100. Using the incidental sampling technique, you are ready to fill out the google form link. The results of this study found that online shopping has a positive effect on consumer loyalty, but online shopping needs encouragement from content marketing and price discounts that make consumers interested. The finding from moderation is that consumer pleasure weakens the effect of content marketing on online shopping, although not significantly. Meanwhile, consumer pleasure strengthens the effect of price discounts on online shopping, although it is not significant. Based on this research, it is proven that discounted prices are more attractive to consumers because they can perform efficiently during this pandemic.